2013
DOI: 10.4187/respcare.02732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Usual and Alternative Methods to Measure Height in Mechanically Ventilated Patients: Potential Impact on Protective Ventilation

Abstract: BACKGROUND: Protective ventilation implementation requires the calculation of predicted body weight (PBW), determined by a formula based on gender and height. Consequently, height inaccuracy may be a limiting factor to correctly set tidal volumes. The objective of this study was to evaluate the accuracy of different methods in measuring heights in mechanically ventilated patients. METHODS: Before cardiac surgery, actual height was measured with a height gauge while subjects were standing upright (reference met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 47 publications
4
23
2
Order By: Relevance
“…This is similar to the results of Bojmehrani et al 5 (visual height ϭ 169.6 cm, tape measure height ϭ 169.4 cm, ulnar-based height ϭ167.2 cm). Their study concluded that in com- parison with the reference method, estimating the height visually and using the tape measure (potential sources of our EHR data) were less accurate than ulnar-based measurements.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is similar to the results of Bojmehrani et al 5 (visual height ϭ 169.6 cm, tape measure height ϭ 169.4 cm, ulnar-based height ϭ167.2 cm). Their study concluded that in com- parison with the reference method, estimating the height visually and using the tape measure (potential sources of our EHR data) were less accurate than ulnar-based measurements.…”
Section: Discussionsupporting
confidence: 81%
“…However, visual estimates and even bedside tape measurements of height in ventilated patients may be inaccurate. 5 A possible alternative source of data is the height predicted by ulnar length. 6 The purposes of this study were (1) to evaluate the difference between patient height of unknown origin charted in the EHR and height based on ulnar length and (2) to determine the effect of the height difference in setting lung-protective V T during mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent observational trials have demonstrated that height is often overestimated to the detriment of some patients, especially in the case of short and obese females. [5][6][7] The low frequency of heelto-crown height measurements in patients with ARDS is probably due to multiple factors, including time, perceived inaccuracy of height measurements in a critically ill supine patient, and a lack of appreciation that accurate height measurements can alter mortality.The study by Jurecki et al 8 explores the complexity of setting low V T for the purpose of lung-protective ventilation; the variation in estimated set V T depends on height estimates which may vary considerably depending on the source used to estimate height. The authors found that, for the study population, the mean height obtained from the electronic health record is similar to the mean predicted height calculated from ulnar length.…”
mentioning
confidence: 99%
“…Subsequent observational trials have demonstrated that height is often overestimated to the detriment of some patients, especially in the case of short and obese females. [5][6][7] The low frequency of heelto-crown height measurements in patients with ARDS is probably due to multiple factors, including time, perceived inaccuracy of height measurements in a critically ill supine patient, and a lack of appreciation that accurate height measurements can alter mortality.…”
mentioning
confidence: 99%
“…The article by Dr Bojmehrani and colleagues published in the present issue of RESPIRATORY CARE perfectly fits this context. 5 They studied the potential impact of differently measured heights on protective ventilation by comparing usual (estimation or tape measurement while patient is supine) and alternative (based on lower leg and forearm dimensions) measuring methods. Height measured in the upright position served as the accepted standard.…”
mentioning
confidence: 99%